2019
DOI: 10.1002/ijc.32507
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of KRAS, NRAS, BRAF, PIK3CA and TP53 mutations in a large prospective series of locally advanced rectal cancer patients

Abstract: Little information is available on the clinical significance of cancer‐related genes such as KRAS, NRAS, BRAF, PIK3CA and TP53 in nonmetastatic rectal cancer. We investigated mutations of these genes in a large prospective series of locally advanced rectal cancer (LARC) patients who were recruited into two phase II trials. Mutational analyses were performed with diagnostically validated methods including polymerase chain reaction, capillary electrophoresis single‐strand conformational analysis, Sanger sequenci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
19
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(23 citation statements)
references
References 52 publications
3
19
0
1
Order By: Relevance
“…**** p-value < 0.0001; *** p-value < 0.001; ** p-value < 0.01, * p-value < 0.05. www.oncotarget.com infiltration by CD8+ T cells [32]. TP53 mutation was the most common molecular alteration in our patient population and was associated with worse survival, similar to its known association with unfavorable outcome in solid and hematologic malignancies [33][34][35][36]. Our data demonstrate that while TP53 mutations are associated with unfavorable survival, the effect of ICB therapy is not diminished by the presence of this gene mutation.…”
Section: Discussionsupporting
confidence: 80%
“…**** p-value < 0.0001; *** p-value < 0.001; ** p-value < 0.01, * p-value < 0.05. www.oncotarget.com infiltration by CD8+ T cells [32]. TP53 mutation was the most common molecular alteration in our patient population and was associated with worse survival, similar to its known association with unfavorable outcome in solid and hematologic malignancies [33][34][35][36]. Our data demonstrate that while TP53 mutations are associated with unfavorable survival, the effect of ICB therapy is not diminished by the presence of this gene mutation.…”
Section: Discussionsupporting
confidence: 80%
“…In daily practice, the biopsy is still the routine way to get tumour mutant status before treatment. Considering the spatial and temporal intra-tumour molecular heterogeneity, the results for biopsy samples are yet to be consistent [11][12][13]50]. Recently, a large prospective study [50] showed that the concordance ratio between paired biopsy and resection specimens was 82% for KRAS status.…”
Section: Discussionmentioning
confidence: 99%
“…Considering the spatial and temporal intra-tumour molecular heterogeneity, the results for biopsy samples are yet to be consistent [11][12][13]50]. Recently, a large prospective study [50] showed that the concordance ratio between paired biopsy and resection specimens was 82% for KRAS status. In the current study, although the best sensitivity (Variance) and specificity (Mean) of the texture features were both over 83% in the study, the sensitivity and specificity of GLNU, which harboured the best diagnostic significance (AUC = 0.813), were both lower than 80%.…”
Section: Discussionmentioning
confidence: 99%
“…It may be speculated that MPN patients with PPM1D mutations may be more prone to development of second cancer. Importantly, several other MPN-associated mutations such as ASXL1, SH2B3, TET2, JAK2, TP53, KRAS, NRAS, and U2AF1 are found in other cancers as well [92,[202][203][204][205]. Indeed, studies have shown that patients with MPNs have a higher risk of developing second cancer [206][207][208].…”
Section: Tp53 and Ppm1d Mutationsmentioning
confidence: 99%